Designing Islamic Religious Education Teaching Based on Digital Innovation Creativity at Universitas Islam Negeri Antasari Banjarmasin - M. Ramli (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2022)
Designing Islamic religious education teaching based on creative digital application innovations in high rooms was an exciting and vital issue to study. For this reason, this study has met many academics from the state Islamic University of Antasari for us to hear their opinions, thoughts, and perspectives on how to design creative and innovative technology-based Islamic learning. The researcher recorded their thoughts and voices through question-and-answer, semi-chartered interviews with seven speakers, then collected the data. The researcher examined it with a phenomenological approach, namely, trying to understand some interview data to answer the problems of this study. The study process involves a phenomenological approach that coding the evaluation and interpreting the data in order to answer the problems. In addition, searchinf the data on secondary publications was also be carried out electronically with the same treatment. It examined them to get their thoughts and problem formulation. Based on the answers and analysis, it  concluded that designing Islamic religious learning with technological innovation and creativity has been done effective at Antasari State Islamic University. The technology has innovated learning creatively to produce was very high output. Keywords:  Designing Islamic Education, Digital Innovation Creativity,  Islamic Religious Education